Correction: Cold shock induces apoptosis of dorsal root ganglion neurons plated on infrared windows. Issue 18 (21st September 2015) - Aboualizadeh, Ebrahim; Mattson, Eric C.; O'Hara, Crystal L.; Smith, Amanda K.; Stucky, Cheryl L.; Hirschmugl, Carol J.
<x xml:space="preserve">Abstract</x> Correction for 'Cold shock induces apoptosis of dorsal root ganglion neurons plated on infrared windows' by Ebrahim Aboualizadeh et al., Analyst, 2015, 140, 4046–4056.